A Novel Elastomer of Starch-Polyvinyl Alcohol Double-Networks for Real-Time of Monitoring Strain, Temperature and Humidity. Issue 211 (12th October 2020) - Xin-Feng, Zhu; Lin-Wei, He; Hao-Ran, Liu; Hui-Lin, Yang; Xiao, Lin; Lei, Yang
Abstract: Artificial electronic skin and wearable sensor are mainly based on the technology of flexible sensors responding to environmental stimuli. This research develops a new elastomer of starch-polyvinyl alcohol double network with high flexibility and sensing capability. The starch-polyvinyl alcohol elastomer (SPE) enables accurate monitoring of strain, temperature and humidity changes with high precision. The gauge factor of SPE for strain reached 1.67, and the sensitivities to temperature and humidity reached 8.48 × 10 −6 S/cm per Celsius degree and 9.9 × 10 −6 S/cm per RH%, respectively. These characteristics make SPE a promising candidate for artificial electronic skin and wearable sensors.